Quantitative assessment of the effect of fasting on macular microcirculation: an optical coherence tomography angiography study. Issue 8 (29th October 2019) - Karaküçük, Yalçın; Beyoglu, Abdullah; Çömez, Ayşegül
Abstract : Aim: To analyse the effect of fasting on the retinal vascular plexus and choriocapillaris structures in healthy subjects via Optical Coherence Tomography Angiography (OCTA). Methods: In this prospective study, OCTA scans of 98 eyes in 49 healthy subjects were compared in fasting and non-fasting period. All cases had a full ophthalmological examination, with OCTA parameters measured, including superficial flow area (SCP) (mm 2 ), deep flow area (DCP) (mm 2 ), choriocapillaris flow area (CC) (mm 2 ), superficial and deep vascular density (SVD and DVD, respectively) (%), superficial foveal avascular zone area (FAZs) (mm 2 ), deep foveal avascular zone area (FAZd) (mm 2 ), subfoveal choroidal thickness (SFCT) (µm) and central macular thickness (CMT) (µm). Results: The mean SCP, DCP and CC flow area values were induced to be significantly lower in a fasting than a non-fasting period (p<0.001, p<0.001, p=0.049, respectively). The mean VD in a fasting period was statistically significantly lower than in a non-fasting period at the SCP level (p=0.009). No statistically significant difference was found between the two periods in respect to DVD, FAZd and CMT (p=0.068, p=0.653 and p=0.531, respectively); however, FAZs were significantly lower in a non-fasting than fasting period (p=0.038). The SFCT was determined to be statistically significant and thicker during a fasting period (p<0.001). Conclusion: The current study documented several physiological changes in a fasting period, such as changes in SCP, DCP, CC flow, SVD and DVD, via OCTA.